2014
DOI: 10.1136/thoraxjnl-2013-204815
|View full text |Cite
|
Sign up to set email alerts
|

The association between childhood asthma and adult chronic obstructive pulmonary disease

Abstract: Introduction There is epidemiological evidence to suggest that events in childhood influence lung growth and constitute a significant risk for adult COPD. The aim of the study is to evaluate for an association between childhood asthma and adult COPD. Methods This longitudinal, prospective study of 6-7-year-old children with asthma has been regularly reviewed every 7 years to the current analysis at 50 years of age. Participants completed respiratory questionnaires and lung function spirometry with postbronchod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
190
1
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(202 citation statements)
references
References 36 publications
5
190
1
6
Order By: Relevance
“…They comprised 6 birth cohorts [17][18][19][20][21][22] and 19 population-based longitudinal studies. [12,13,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Tables 1 and 2 give an overview of the included studies. The reasons for rejecting the remaining 30 papers [9,10, are summarised in Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They comprised 6 birth cohorts [17][18][19][20][21][22] and 19 population-based longitudinal studies. [12,13,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Tables 1 and 2 give an overview of the included studies. The reasons for rejecting the remaining 30 papers [9,10, are summarised in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…[12,13] The vast majority of those with COPD aged 50 years came from the severe asthma group recruited at 10 years of age.…”
Section: Page 13 Of 24mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies involving children and young adults have shown that the most important determinant of maximally attained lung function later in life was the lung-function value at a younger age. [26][27][28][29] Svanes et al observed that childhood risk factors such as maternal smoking, childhood respiratory infections, and childhood asthma were strongly related to the development of COPD in young adults. 30 Nevertheless, although our results highlight the important role of maximally attained lung function in early adulthood, Shown is the distribution of observed annual decline in forced expiratory volume in 1 second (FEV 1 ) among 2864 participants in the Framingham Offspring Cohort (FOC) and the Copenhagen City Heart Study (CCHS), according to the four trajectories defined on the basis of a normal FEV 1 (≥80% of the predicted value) or low FEV 1 (<80% of the predicted value) at baseline and the presence or absence of chronic obstructive pulmonary disease (COPD) at the final examination.…”
Section: Discussionmentioning
confidence: 99%
“…To muddy the waters further, the presence of fixed airways obstruction is not uncommon among nonsmokers [108,109]. A proportion of these cases are probably untreated asthma, the result of airway remodelling in chronic asthma despite treatment or of severe childhood asthma [110,111]. In the recent BOLD (Burden of Obstructive Lung Disease) initiative [112], the occurrence of post-bronchodilator airflow limitation found during screening of population-based samples has been termed COPD, regardless of potential aetiological factors such as smoking, asthma or childhood respiratory disease.…”
Section: Copd Phenotypes or How To Predict Which Patients Benefit Fromentioning
confidence: 99%